Photography after photography : gender, genre, and history - Solomon-Godeau, Abigail (Duke University Press, 2017)
In essays analyzing the photography of luminaries such as Cindy Sherman, Robert Mapplethorpe, and Susan Meiselas, pioneering feminist art critic Abigail Solomon-Godeau extends her politically engaged and theoretically sophisticated inquiry into the historical and cultural circuits of power as they shape and inform the practice, criticism, and historiography of photography